(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
In this article, based on the poetic observations of the Uzbek poet Gafur Ghulam about the great Eastern poets Nizami and Mahasti, certain generalizations were made about the historical and genetic roots of the age-old friendship and brotherhood between the Uzbek and Azerbaijani peoples. Common and unique aspects of the philosophical-aesthetic concept of Samad Vurgun and Gafur Ghulam are researched based on the ideas of literary traditions, succession, creative cooperation, and inter-ethnic friendship. A poem written by G. Ghulam dedicated to Samad Vurghun was widely analyzed. The views advanced in the article are summarized